Strategi Adaptasi dalam Huntap Karang Kendal, Dusun Balong, Desa Umbulharjo, Kecamatan Cangkringan, Kabupaten Sleman Daerah Istimewa Yogyakarta - , Bambang Pramono, S.S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As a topdown design policy, most of post-disaster permanent house requiring adaptation behavior of it occupans. The limitaion on space of phycical and spatial setting lead to adaptation strategy choices. Local policy was applied on placing people configuration, a blood-tied based where parent placed next to heritance. Since this reseach intense to explore the adaptation behavior, which is focusing on adaptation strategy choices of Karang Kendal Setlemen, a qualitative naturalistic reseach method with inductive analysis were applied, The single shared-kitchen phenomenom found as result, folllowing by adaptation by reaction as choosen strategy. An assumsion yield as result that kinship parent-children relationship as the key factor of this spatial setting behavior